2019
DOI: 10.1007/s11837-019-03919-5
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Electron Diffraction Investigation of Solid State Synthesis of Co-In2O3 Ferromagnetic Nanocomposite Thin Films

Abstract: In situ electron diffraction was used to study structural transformations during the formation of Co-In 2 O 3 ferromagnetic nanocomposite thin films in a thermite reaction of In/Co 3 O 4 bilayer thin films. Heating was performed from room temperature to 600°C at a rate of 4°C/min, while simultaneously electron diffraction patterns were recorded at a speed of 4 frames/min. This made it possible to determine the initiation, 185°C, and finishing, 550°C, temperatures of the solid-state synthesis, as well as the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The analysis of the obtained electron diffraction patterns allowed determining the sequence of phase transformations occurring in the solid-state reaction between dissimilar nanolayers. The authors successfully used the method to investigate the process of phase formation during the solid-state reaction in different thin-film nanosystems: Al/Cu [ 25 , 26 ], Al/Pt [ 27 ], Al/Ag [ 28 , 29 ], Cu/Au [ 30 ], Al/Fe [ 31 ], Fe/Si [ 32 ], Fe/Pd [ 30 , 33 , 34 ], Fe-ZrO 2 [ 35 ], Co-ZrO 2 [ 36 ], and Co-In 2 O 3 [ 37 ]. In the present study, in order to estimate the kinetic parameters of the solid-state reaction (activation energy, pre-exponential factor, and reaction order), a series of heating procedures was performed at different rates.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of the obtained electron diffraction patterns allowed determining the sequence of phase transformations occurring in the solid-state reaction between dissimilar nanolayers. The authors successfully used the method to investigate the process of phase formation during the solid-state reaction in different thin-film nanosystems: Al/Cu [ 25 , 26 ], Al/Pt [ 27 ], Al/Ag [ 28 , 29 ], Cu/Au [ 30 ], Al/Fe [ 31 ], Fe/Si [ 32 ], Fe/Pd [ 30 , 33 , 34 ], Fe-ZrO 2 [ 35 ], Co-ZrO 2 [ 36 ], and Co-In 2 O 3 [ 37 ]. In the present study, in order to estimate the kinetic parameters of the solid-state reaction (activation energy, pre-exponential factor, and reaction order), a series of heating procedures was performed at different rates.…”
Section: Methodsmentioning
confidence: 99%
“…[30,31] This above-mentioned method was successfully used by the authors for the research of structural phase transformations occurring in the solid state reaction process in various thin film nanosystems: Cu/Au, [32] Al/Pt, [33] Fe/Pd, [32,34,35] Fe/Si, [36] Fe-ZrO 2 , [37] Co-ZrO 2 , [38] Co-In 2 O 3 . [39] In order to carry out in situ experiments with heating in the transmission electron microscope, the samples deposited on NaCl, immediately after the deposition, were separated from the substrate by submerging them into aquabidest for several seconds, then the films rose to the surface and were placed onto a molybdenum TEM support grid, with the remaining water being immediately removed with filter paper. The absence of defects (exfoliation) in the films after placing them onto the grid was controlled with an optical microscope Nikon Eclipse LV 100.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of pure In 2 O 3 nanoparticles had been performed via solid state reaction method for the fabrication of optoelectronic devices by Jothibas et al [57]. Moreover, Bykova et al [58] reported Co-In 2 O 3 nanocomposites thin film by solid-state reaction method and investigated its structural and magnetic properties. Recently, Co-In 2 O 3 nanocomposites and cobalt-doped In 2 O 3 have attracted significant attention due to their applications in optoelectronic, spintronic devices and gas sensors [58].…”
Section: Solid State Reactionmentioning
confidence: 99%